TEOLOGI PENDERITAAN: MAKNA SALIB BAGI ORANG KRISTEN YANG MENDERITA - Aminah Cendra Kasih Bate’e; Tony Salurante (Social Studies and Humanities Journal (SOSHUM), 2025)
This study aims to develop a theological synthesis that positions the cross as a comprehensive paradigm for understanding and responding to suffering in Christian life, going beyond a purely soteriological focus and addressing the existential and collective dimensions of suffering in the contemporary era. The study employs a narrative review approach with theological hermeneutical analysis. The literature is categorized into biblical foundations, classical theological traditions (Augustine, Luther, Calvin, Barth, Bonhoeffer, Moltmann), and contemporary theologies (liberation, contextual, trauma), selected based on relevance to issues of suffering, the theology of the cross, and contemporary contexts, then analyzed to identify continuity and development in theological reflection. The findings indicate that the cross biblically represents divine solidarity in human suffering (Philippians 2:5–11; 1 Peter 2:21) and serves as a means of glorification (Romans 8:17). Classical traditions view suffering as pedagogical (Augustine), a locus of God’s presence (Luther), and part of providence (Calvin). Modern and contemporary theologies relate the cross to God’s solidarity with the oppressed (Moltmann), the struggle against injustice (Gutiérrez), and psychosocial restoration (trauma theology). This synthesis affirms the cross as a multidimensional paradigm of suffering that nurtures resilient spirituality, ethical transformation, and social solidarity. The study proposes a conceptual framework of a Christ-centered suffering paradigm that integrates soteriological, pastoral, and social justice dimensions, relevant for pastoral practice and contemporary academic dialogue.